Long-term effects of whole-body vibration training in high-level female basketball players - Fernandez-Rio J.; Terrados N.; Suman O. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM:The aim of this study was to investigate the long-term effects of Whole-Body Vibration (WBV) training on the jumping capabilities of high-level female basketball players. METHODS: A 12-week WBV program was applied to 10 national and international level female basketball players. They were randomly distributed into a control group (CG: 23.2±3.96 years, 69.64±11.17 kg, 179.7±7.96 cm) and an experimental group (VG: 24.0±2.65 years, 70.17±9.86 kg, 181.9±10.83 cm). In order to determine the effects of the WBV program on the jumping capabilities of the subjects, the following tests were used: SJ, CMJ, ACMVJ, and 15-seconds maximal jump. RESULTS: In the SJ test, the CG significantly increased from 455.4±25.91 to 476.6±26.6 ms (+4.42%; P=0.05), while the VG also increased significantly from 455±15.62 to 478.33±16.56 ms (+5.13%; P=0.02). In the CMJ test, the CG significantly increased from 470.2±12.15 to 496±23.38 ms (+5.49%; P=0.04), while the VG remained unchanged: 472±15.62 to 474.67±8.74 ms (+0.76%). In the ACMVJ test, the CG increased from 514±37.67 to 520±15.5 ms (+1.42%), while the VG decreased from 515±31.43 to 510.33±16.56 ms (-0.77%). In the 15-seconds jump test, the CG increased from 459±23.48 to 481.6±15.53 ms (+5.15%), while the VG increased from 464±36.66 to 471±33.96 ms (+1.6%). In this same test, the power generated by the CG increased from 20.01±1.84 to 22.14±2.21 W/kg (+11.12%), while the VG increased from 17.28±2.39 to 22.21±5.82 W/kg (+29.7%). CONCLUSION: WBV has no extra appreciable effect or benefit on the jumping capabilities of high-level female basketball players compared to regular strength training methods.